The impact of the Covid-19 pandemic on work contracts in the peruvian reality - Torres-Calderón Z., Cesar (2020)
A brand new panorama is presented in the world, due to the presence of the spread of COVID- 19 that has generated a new form of coexistence, the law has not been the exception to the transformations arising legal conflicts, specifically in the law of contracts, in regarding the work contract where the new behaviors of the subjects involved have affected, the peculiar breaches due to an event of force majeure that interrupts a normal development of a construction contract, which affects the termination of contracts, which it is the impact of the binding force and government restrictions or limits on workers, as well as the impact of state measures on construction contracts. Hence, the purpose of our study is to determine how the impact of the Covid-19 pandemic on construction contracts in Peruvian reality. It is a qualitative approach work, since it will use the methods of observation and analysis of texts.